(untitled) - Garrity, George M. (New York, 2001)
Arrangement of the content of the Second Edition follows the now familiar and well regarded phylogeny of the 16S rRNA gene, yet retains much of the layout of the First Edition. Volume 1, encompasses. Volume 2 covers Proteobacteria. At present, there are roughly 6250 named species of Bacteria, and the Proteobacteria represent the single largest phylum. Encompassing 72 families and including descriptions of 425 genera and over 1875 named species, this volume is subdivided into three sub-volumes: The Gammaproteobacteria (Part A), The Alphaproteobacteria (Part B) and the Beta, Delta, and Epsilonproteobacteria. Also included are new introductory chapters specific to the phylum. Medically important species appear in all three sub-volumes. Volume 3 covers Firmicutes.
Vi sinh học đại cương,Vi sinh vật nâng cao
Keywords: Bacteria,Vi khuẩn; Classification,Phân loại